2012
DOI: 10.1017/s1368980012003953
|View full text |Cite|
|
Sign up to set email alerts
|

Association between vitamin B12intake and EURRECA's prioritized biomarkers of vitamin B12in young populations: a systematic review

Abstract: Objective: To review evidence on the associations between vitamin B 12 intake and its biomarkers, vitamin B 12 intake and its functional health outcomes, and vitamin B 12 biomarkers and functional health outcomes. Design: A systematic review was conducted by searching electronic databases, until January 2012, using a standardized strategy developed in the EURRECA network. Relevant articles were screened and sorted based on title and abstract, then based on full text, and finally included if they met inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 147 publications
0
2
0
1
Order By: Relevance
“…In a systematic review on the associations between cobalamin intake and biomarkers in children (Iglesia et al, 2013), one cross-sectional study was identified which examined dietary intake of cobalamin and serum cobalamin, holoTC, MMA and tHcy concentrations in 155 healthy, non-breastfed Norwegian toddlers at 24 months of age (Hay et al, 2011). Seven-day weighed food records were used for cobalamin intake assessment.…”
Section: Infants and Childrenmentioning
confidence: 99%
“…In a systematic review on the associations between cobalamin intake and biomarkers in children (Iglesia et al, 2013), one cross-sectional study was identified which examined dietary intake of cobalamin and serum cobalamin, holoTC, MMA and tHcy concentrations in 155 healthy, non-breastfed Norwegian toddlers at 24 months of age (Hay et al, 2011). Seven-day weighed food records were used for cobalamin intake assessment.…”
Section: Infants and Childrenmentioning
confidence: 99%
“…The common view is that cobalamin deficiency is more likely to occur when IF-driven absorption fails (pernicious anemia) than when diet is poor (vegetable diet). However, attention has been restricted to elderly people, while there is a lack of information on vitamin B 12 deficiency in young populations [24]. One study has shown that 40% of vegetarians presented with lower blood Hb concentration, hematocrit, mean corpuscular Hb mass and serum cobalamin levels than the control subjects [48].…”
Section: Cobalamin Deficiencymentioning
confidence: 99%
“…No entanto, ela é influenciada por diversos fatores, tal como massa muscular, e sua confiabilidade como biomarcador precisa ser mais bem determinada227 . Os componentes Vegetal total SL e Veveal SL apresentaram ainda De fato, as concentrações plasmáticas de vitaminas do complexo B não são relacionadas apenas ao consumo dos alimentos fontes, mas também aos padrões alimentares237,238 . Além das correlações positivas encontradas entre componentes do IQD-R considerados fontes de vitaminas do complexo B e seus biomarcadores, correlações negativas foram encontradas entre esses e os componentes Carne, ovos e leguminosas, Gordura saturada e Cereal total.…”
unclassified